Localisation of genes controlling resistance to trypanosomiasis in mice - Kemp, Stephen J.; Iraqi, F.A.; Darvasi, A.; Soller, M.; Teale, A.J. (Springer, 1997)
Tsetse fly-transmitted trypanosomes (Trypanosoma spp.) cause 'sleeping sickness' in man and have a serious impact on livestock-based agriculture in large areas of Africa. Multigene control of variation in susceptibility to trypanosomiasis is known to occur in mice, where the C57BI/6 (B6) strain is relatively resistant and the A/J (A) and Balb/c (B) strains are susceptible. Such resistance is also well described among several types of west African cattle. We report here the results of genome-wide scans for genes controlling this trait in the B6 mouse using crosses with two different susceptible strains. Regions on mouse chromosomes 5 and 17 were found to be important in determining resistance in both crosses while an additional region on chromosome 1 showed evidence of involvement in only one cross. We confirmed the size of the effect due to chromosome 17 in F3 intercross populations fixed for alternative parental chromosomes. The three loci are of large effect and account for most of the genetic variation in both F2 populations. We propose that they be designated Tir1, Tir2 and Tir3.